Soft Selling Communications Strategies in Building Brand Awareness for “Sasa” on Raditya Dika’s YouTube Account Content - Ilham Baihaqi; Salsabila Cahyarani; Farida Nurfalah (Apollo: Journal of Tourism and Business, 2025)
Marketing in the modern era, namely soft selling, is characterized by the use of digital technology and a more personal approach. This research aims to find out the soft selling communication strategy applied by Sasa in building brand awareness, especially in the promotion of vetsin (MSG) through collaboration with Raditya Dika on YouTube in the content "Who Likes Micin, Watch This!". The research focus includes the target audience, message, method, communicator, media, and communication effects in this promotion. The writing method used is qualitative through a post-positivism approach, with the subject studied being the "Sasa" brand as an entity that implements soft selling communication strategies. The results prove that education-based soft selling communication strategy can be an effective method in building brand awareness and changing public perception of a product. Brand Sasa successfully utilizes digital communication and the right media selection to create an emotional connection by providing educational value for its audience.